Computed tomography angiography in anomalous left coronary artery from pulmonary artery: a case series - Guleria, Munish; Arora, Suryansh; Jadon, Ravindra Singh; Sana, Sana; Yadav, Pritam; Singh, Shreshtha (International Journal of Contemporary Pediatrics, 2022)
Anomalous left coronary artery from pulmonary artery (ALCAPA) is a rare congenital anomaly with a high rate of mortality in first year of life. It is one of the most common causes of cardiomyopathy and myocardial ischemia in children. In the present scenario, computed tomography (CT) coronary angiography is sufficient for the diagnosis of ALCAPA, eliminating the need of invasive angiography. CT coronary angiography performed in infants with suspicion of ALCAPA is technically challenging in terms of acquisition techniques, radiation protection and diagnostic interpretation. In this case series, we present five cases of ALCAPA diagnosed on CT coronary angiography. CT coronary angiography was able to delineate the anomalous origin of left coronary artery (LCA) from pulmonary artery in all cases. Anomalous LCA was noted to arise from posterior pulmonary sinus of pulmonary trunk in four cases and main pulmonary artery in one case. CT angiography also identified the extent of inter-coronary collateral vessels, left ventricular dysfunction and signs of pulmonary hypertension.